The importance of intergenerational play to selected day care parents - Ilagan, Merry Joy R.; Dy, Marison R. (2014)
This study aimed to determine the knowledge and attitudes of day care parents on play with their children, identify the level of importance they give to play with their children, and to relate their socio-demographic characteristics to the level of importance given to play with their children. A questionnaire was administered to 45 respondents from three barangays. Findings showed that parents saw play as a form of recreation and a learning process. The most common play activity that the respondents engaged in with their children was dramatic play and play duration with their child was usually for less than an hour. Fifty-eight percent stated that playing with their children was important to them. It was determined that the scores of the respondents for the importance given to parental play with children were mostly on the average level. All the correlations between the scores and quantitative socio-demographic characteristics (e.g. age, income, educational attainment, number of children, and number of hours given to parental play with children) resulted to weak positive correlations. None of the relationships were statistically significant. Still, parental play with children leads to positive developmental outcomes. Further studies with a larger and more diverse sample can be done to better look into intergenerational play as a social context for child development.
Keywords: Day care -- Parents; Intergenerational play